Challenges, opportunities, and strategies for undertaking integrated precinct-scale energy–water system planning. (June 2022) - de Oliveira, Glauber Cardoso; Bertone, Edoardo; Stewart, Rodney A.
Abstract: The energy and water sectors are intrinsically linked to meet several consumer needs. A holistic analysis is required to quantify the technoeconomic and environmental benefits and impacts of energy–water interactions. Despite ongoing investigations into assessing the integrated energy and water resource use such as those covered in this review paper, the energy–water nexus linkages seem to remain analytically undefined in a systemic relationship to assess trade-offs among different objectives of energy and water usage, thereby revealing synergies between energy and water. Given an observed lack of quantitative assessments of integrated energy and water resource use in local sites such as urban precincts, the present study comprehensively reviewed literature covering energy and water systems, technologies, management measures, schemes and approaches for integrated planning at various scales. Planning challenges were identified for energy and water system integration at precinct scale. To advance state-of-the-art applications, this paper proposes research directions for integrated precinct-scale energy–water system planning. In addition, planning opportunities for integrated energy and water systems were identified towards precinct-scale deployments. Several findings indicated critical roles of complex inter-building effects from precinct elements with energy–water system interdependencies. In urban precincts, integrated energy and water system plans could enhance resource sustainability at a lower cost. The strategic approach outlined in this paper will help facility custodians to optimise complex energy–water portfolio capital investments for precinct-scale developments, including available retrofit projects supported by appropriate financing options. Highlights: Enabling energy–water system integration to move towards sustainable urban precincts. Managing polygeneration key to enhance renewable energy and nonpotable water usage. Coupling energy–water resource distribution networks boosts energy–water cost savings. Deploying decentralised community microgrids augments energy–water system flexibility. Driving integrated energy–water system plans for robust optimal investment portfolios.